Ease of Doing Business and Capital Market Development in a Demand Following Hypothesis: Evidence From Ecowas - Nager, Kamaldeen Ibraheem (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2020)
Capabilities of African businesses in a transformative role in solving the continent‘s challenges are underestimated and misunderstood. This study examined ease of doing business and financial development from a demand following hypothesis in the West African sub-region, employed Structural Equation Model covering the period of 2004 - 2017. Ten ease of doing business indicators and five distinct financial (capital market) development variables from the World Bank database were used. Findings indicate weak demand following the hypothesis of capital market development: positive and negative, depending on the measure of capital market development from the ease of doing business for West African countries majorly because of inadequate electricity. The indirect effect of the construction permit, property registration, access to credit, minority investors‘ protection and cross-border trading are indirectly significant to capital market development while starting a business, tax-paying, contract enforcement and settling insolvency are insignificant. The study recommended roadshow by West African capital markets to improve the listing of companies and the government should improve on the electricity supply.